Study of wave forces on small-scale structural elements - Tan, Yong Ming. (2013)
The study was motivated by the need to understand tsunami-like wave impact forces on different orientations of typical structural elements. Two experiments were designed to understand the effects of the designs of different structural elements and the transmitted load due to the wave impact loading. The study made use of highly sensitive pressure transducers and strain gages to identify different loading conditions present; which includes strain on the target as well as the transmitted wave height. Simulated wave forces were generated by lifting up a dam-gate which separates the shallow water from a large volumetric tank. The first experiment used a single pressure target to identify the pressure distribution on structural element found without a simulated seabed. The second lab experiment made use of four strain targets, specially designed for the investigating of the transmitted wave force on structural elements at different orientations. The targets included a flat-faced, angled-oriented, semi-circular shaped as well as an elevated stilt target. They were also used to identify the optimal design for minimum transmitted wave force. A close examination of the resultant strains of different targets shows that the elevated stilt target experienced the least amount of strain, followed by an angled-oriented target. Despite the smooth curvature of the semi-circular target, an interesting comparison between strain results showed that the semi-circular target experienced a larger force as compared to the angled-oriented target. Through the small-scaled wave impact test model experiment, the relationship between the different structural targets and angles on the transmitted wave forces were established. Furthermore, an ideal coastal structural design was proposed – a structure combining the features of the angled and the stilt targets.